Statistics anxiety among diploma in wood technology students at Universiti Teknologi Mara / Suriyati Ujang...[et.al.] - Ujang, Suriyati; Asmat, Aszila; Razak, Mohd Rizal; Syed Wahid, Sharifah Norhuda (Universiti Teknologi MARA Cawangan Pahang, 2014)
Mathematics performance especially in the statistical field is still an issue among students in higher learning institution. Students have learnt probability topic in the mathematics subject since SPM level, but they have a bad perception towards the statistics subject at higher learning institutions because of their bad experiences before. Therefore, the main focus of this paper is to examine the statistics anxiety level and its association with probability topic. 103 students from the science stream who were studying at one of the public universities in Malaysia were selected. The findings show that there is an association between students’ opinion towards probability topic and the four predictors; students’ self-confidence, class environment, self-concept and study techniques, with 63.50% of total variation. In addition, it was found that any positive improvement in any of the predictors will lead students to have better opinion towards the probability topic in the statistics course. Thus, the finding of this study is hoped to provide useful information in helping students maximize their potential in statistics courses.